READINESS OF THE DIGITAL ECOSYSTEM/ENVIRONMENT IN GORONTALO IN ENCOURAGING PUBLIC SERVICES TO GO DIGITAL IN THE ERA OF SOCIETY 5.0s - Suparno, Suparno; Kamuli, Sukarman (Universitas Negeri Gorontalo, 2022)
The current rapid development of information technology has encouraged various sectors to shift from manual to digital, especially in the era of the pandemic. If the private sector is able to adapt to the massive use of digital technology, what about the government sector? The method in this study uses descriptive analysis of secondary data from various surveys and in-depth interviews at the Department of Information, Communication, and Statistics of Gorontalo Province. The digital ecosystem in the Gorontalo community is considered quite ready to enter the digital era. This can be seen from the coverage of digital infrastructure which has reached 93.3 percent of villages that have been served with an internet signal. A total of 72.68 percent of households have access to a cellular phone. In 2020, as many as 76. 68 percent of Gorontalo households have been accustomed to accessing the internet. On the other hand, the government has also begun to prepare digital public services, this can be seen from the Gorontalo Province SPBE index value in 2019 which has reached a value of 3.18 with a good predicate, although at the Regency / City level it is still categorized as sufficient a nd lacking. People who are getting easier to get information and are getting smarter, are starting to demand easy and quality public services. So that the government needs to be encouraged to digitize public services in order to be able to meet various demands in the current technological era. this can be seen from the Gorontalo Province SPBE index value in 2019 which has reached a value of 3.18 with a good predicate, although at the Regency / City level it is still categorized as sufficient and lacking. People who are getting easier to get information and are getting smarter, are starting to demand easy and quality public services. So that the government needs to be encouraged to digitize public services in order to be able to meet various demands in the current technological era. this can be seen from the Gorontalo Province SPBE index value in 2019 which has reached a value of 3.18 with a good predicate, although at the Regency / City level it is still categorized as sufficient and lacking. People who are getting easier to get information and are getting smarter, are starting to demand easy and quality public services. So that the government needs to be encouraged to digitize public services in order to be able to meet various demands in the current technological era.